PERUBAHAN GAYA HIDUP ALUMNI PONDOK PESANTREN - Irsyad, Muhammad Habibul; Hufad, Achmad; Malihah, Elly (Sosio Religi: Jurnal Kajian Pendidikan Umum, 2017)
This research is based on alumni of the islamic boarding school which is facing a process of lifestyle adaptation from a different environment as an effect towards integration of the society in the new environment. This research is aimed to describe: a lifestyle changes from student alumni of the islamic boarding school, the factors that affect lifestyle changes and effort of controlling lifestyle to the new social environment. This study utilized a qualitative approach with descriptive methods. The technique of collecting data is by conducting in-depth interviews, participatory observation, literature, and study the documentation. The results showed that: (1) Lifestyle changes of student alumni of the cottage boarding school are happened in the side of doing the leisure activities and using money, as well as the interest in technology, food, recreation, fashion, and promiscuity. (2) Factors behind lifestyle changes includes two factor: Internal and ekstenal. (3) The control of conducted by students alumni of the cottage boarding school for confront a lifestyle at the new environment are: follow the islamic forum, surrond themselves with alumni of the cottage boarding school, and watch the religious video. These three efforts are a form of social control to reach the balance of the impact of change